Produção de mudas de Parapiptadenia rigida (Benth.) Brenan e Luehea divaricata Mart. et Zucc. em diferentes substratos e lâminas de irrigação - Dutra, Adriana Falcão (2012)
Parapiptadenia rigida (mimosa-red) and Luehea divaricata (horse-whips) are native species that are widely distributed throughout Brazil, indicated for restoration of areas that are being recovered and permanent preservation areas. These species have been over-exploited, and yet, still lack of studies related to its conservation and perpetuation. The present study aimed to evaluate the effects of irrigation on the survival and growth of Parapiptadenia rigida and Luehea divaricata seedlings on different substrate types in the nursery. The study was conducted at Forest Nursery, Department of Forest Sciences, Federal University of Santa Maria (UFSM). The fruits of Parapiptadenia rigida were collected in September 2009 in the region of Santa Maria (RS) of 28 trees, and the fruits mature of Luehea divaricata were collected in July 2010 at the Morro Cerrito, Santa Maria, in eight trees matrices. After processing, seeds were stored for later sowing. The sowing of horse-whips and mimosa-red were held on November 22 and December 10, 2010, respectively. For both species, we used a randomized block design with four replications, consisting of factorial scheme, considering six irrigation levels (4, 8, 12, 16, 20 and 24 mm.day-1) and 4 formulations substrates ( 100T: 100% peat 80T: 80% peat and 20% rice hulls; 60T: 60% peat and 40% rice hulls; 40T: 40% peat and 60% rice hulls), whose variables height, diameter, and ratio H/DC were evaluated in time to produce a factorial, and variable survival, dry matter production, leaf area and Dickson Quality Index (IQD), were evaluated only at the last measurement (two-factor). The results allow us to conclude that the 184 days after sowing, the survival of Parapiptadenia rigida and Luehea divaricata were, respectively, 100% and above 93%. Moreover, for the mimosa-red, the blade of 4 mm.day-1 together with the substrate composed of 80% peat and 20% rice hulls gave the best seedling development. For the horse-whips, the blade of 16 mm.day-1 in combination with the substrate composed of 100% peat, provided the best seedling development. Thus, it is recommended daily blades of 4 mm.day-1 and 16 mm.day-1 and substrates 80T and 100T, and to Parapiptadenia rigida Luehea divaricata, respectively, as being ideal for the growth of both species in nurseries .